EKSPLORASI NILAI-NILAI KURIKULUM BERBASIS CINTA SEBAGAI FONDASI PENDIDIKAN KARAKTER DI MADRASAH IBTIDAIYAH - Kholidin; Sunhaji (Jurnal Tawadhu, 2025)
Character education has become a primary focus in fostering student development in Indonesia, particularly at the elementary level in madrasahs, due to the increasing cases of moral degradation in the school environment. This study aims to analyze the integration of character education into the madrasah curriculum through a conceptual review that incorporates theories, policies, and previous research findings. The research employs a qualitative descriptive approach centered on literature review and content analysis. The findings reveal that the incorporation of spiritual and humanistic values serves as a fundamental basis for developing comprehensive character formation, encompassing moral knowing, moral feeling, and moral acting as proposed by Lickona, as well as the process of moral reasoning development according to Kohlberg. The love-based curriculum (KBC) is considered a strategic approach to overcoming the weaknesses of traditional character education, which has been overly focused on cognitive and normative aspects. This curriculum model emphasizes compassion, empathy, and the internalization of values through meaningful learning experiences. The study concludes that policy support, teacher training, and madrasah culture are crucial to ensuring the effective implementation of character education in madrasahs. Further empirical studies are required to examine the effectiveness of this integrative model within the learning context.